PARADIGMA FIQIH SOSIAL KH. M. A. SAHAL MAHFUDH DALAM MENJAWAB PROBLEMATIKA AKTUAL UMAT DI INDONESIA - Moh Dahlan (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2016)
One of the religious movements in Indonesia who care about the fate of the backwardness of the people in its various aspects and  maintenance the tradition  versus  modernist is NU. Therefore,  the presences of NU in addition  to preserve the  understand of Islam of Ahlu Sunnah  wal Jamaah, but also to stem  the  flow of radical religious movements. Therefore, KH MA Sahal Mahfudh as one of the key figures of NU then initiated a paradigm of social jurisprudence to address the problem. Based on this paradigm, the goal of this study was to explore the social paradigm of ijtihad jurisprudence by MA KH Sahal Mahfudh along with social jurisprudence product in addressing the  actual  problems of the  people. The theoretical framework used  is thought  of M Amin Abdullah,  while  the method of this study  is descriptive-analytic study.  The results  show  that  the  paradigm of ijtihad jurisprudence social proposed by KH MA Sahal Mahfudh is built on reason and revelation or naqliyah and aqliyah proportionally, so using the  framework of M Amin Abdullah,  the  paradigm of ijtihad jurisprudence proposed by KH MA Sahal Mahfudh  include  into interconnected entities  approach category  which  where there  is a balance between the use  of aqliyah and  naqliyah  propositionally. The products of the legal jurisprudence was  seen in building social dynamics and the livelihood of the people, both in the field ukhuwah, economics, Siyasah ‘Aliyah Samiyah, as well as the understanding of Aswaja in order to answer the problems of actual people in Indonesia